2019
DOI: 10.3389/fnbeh.2019.00043
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Induces PTSD-Like Memory Impairments via Regulation of the β-Adrenoceptor-cAMP/PKA and CaMK II/PKC Systems in the Basolateral Amygdala

Abstract: Glucocorticoids (GCs) can modulate the memory enhancement process during stressful events, and this modulation requires arousal-induced norepinephrine (NE) activation in the basolateral amygdale (BLA). Our previous study found that an intrahippocampal infusion of propranolol dose-dependently induced post-traumatic stress disorder (PTSD)-like memory impairments. To explore the role of the noradrenergic system of the BLA in PTSD-like memory impairment, we injected various doses of NE into the BLA. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
(101 reference statements)
1
3
0
Order By: Relevance
“…The enhancing effect of acute stress on the generalization of fear (i.e., US expectancies) described in Chapter 3 align well with previous studies that observed an acute stress or cortisol effect on fear generalization in humans (e.g., and animals (e.g., Bender et al, 2018;Kaouane et al, 2012;Kolodziejczyk & Fendt, 2020;Lesuis et al, 2021;Liu et al, 2019;Ren et al, 2022;Zhu et al, 2018). However, a recent study failed to find an effect of acute stress on fear generalization in healthy individuals (Kausche, Zerbes, Kampermann, Büchel, et al, 2021).…”
Section: The Effect Of Stress On Fear and Avoidancesupporting
confidence: 84%
“…The enhancing effect of acute stress on the generalization of fear (i.e., US expectancies) described in Chapter 3 align well with previous studies that observed an acute stress or cortisol effect on fear generalization in humans (e.g., and animals (e.g., Bender et al, 2018;Kaouane et al, 2012;Kolodziejczyk & Fendt, 2020;Lesuis et al, 2021;Liu et al, 2019;Ren et al, 2022;Zhu et al, 2018). However, a recent study failed to find an effect of acute stress on fear generalization in healthy individuals (Kausche, Zerbes, Kampermann, Büchel, et al, 2021).…”
Section: The Effect Of Stress On Fear and Avoidancesupporting
confidence: 84%
“…Its excellent temporal accuracy allowed us to capture yohimbine effects on brief neurophysiological processes during N170 and LPP periods, but little is known about brain circuits mediating noradrenergic actions in humans ( Giustino and Maren, 2018 ). In rats, NE injection into the amygdala immediately after fear conditioning causes PTSD-like memory ( Liu et al, 2019 ). Projections from the locus coeruleus might release NE into the amygdala ( Likhtik and Johansen, 2019 ), or (vice versa) rapid amygdala processing may initiate locus coeruleus responses ( Liddell et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of memory function is seen in a number of stress-associated disorder such as post-traumatic stress disorder (PTSD) ( Berardi et al, 2014 ; Morena et al, 2018 ; Watson, 2019 ). Many studies indicated that the noradrenergic system might be responsible for the persistence of traumatic memories in PTSD ( Debiec et al, 2011 ; Gazarini et al, 2014 ; Liu et al, 2019 ). A hallmark feature of such psychiatric condition is the over-consolidation of the traumatic experience, which in turn leads to maladaptive behavior ( Desmedt et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%